Hydrodynamic simulations of the interaction between an AGB star and a main-sequence companion in eccentric orbits. Issue 4 (30th November 2015) - Staff, Jan E.; De Marco, Orsola; Macdonald, Daniel; Galaviz, Pablo; Passy, Jean-Claude; Iaconi, Roberto; Low, Mordecai-Mark Mac
Abstract: The Rotten Egg Nebula has at its core a binary composed of a Mira star and an A-type companion at a separation >10 au. It has been hypothesized to have formed by strong binary interactions between the Mira and a companion in an eccentric orbit during periastron passage ∼800 yr ago. We have performed hydrodynamic simulations of an asymptotic giant branch (AGB) star interacting with companions with a range of masses in orbits with a range of initial eccentricities and periastron separations. For reasonable values of the eccentricity, we find that Roche lobe overflow can take place only if the periods are ≪100 yr. Moreover, mass transfer causes the system to enter a common envelope phase within several orbits. Since the central star of the Rotten Egg nebula is an AGB star, we conclude that such a common envelope phase must have lead to a merger, so the observed companion must have been a tertiary companion of a binary that merged at the time of nebula ejection. Based on the mass and time-scale of the simulated disc formed around the companion before the common envelope phase, we analytically estimate the properties of jets that could be launched. Allowing for super-Eddington accretion rates, we find that jets similar to those observed are plausible, provided that the putative lost companion was relatively massive.